The Role of Podcasts in Public Opinion Formation in Jordan and the Arab World - Nasereddin, Sara (Journal of Posthumanism, 2025)
Podcasts have become a key medium for information dissemination and public discourse. This study explores their role in shaping public opinion in Jordan and the Arab world, an area less studied compared to traditional media. Using surveys and interviews, the research examines podcasts’ impact on political engagement, media trust, and discourse. Findings suggest that podcasts are viewed as more engaging and reliable than traditional media, fostering critical thinking. However, concerns about misinformation persist. The study provides insights for policymakers and media professionals, highlighting podcast for.